An estimated model of a commodity-exporting economy for the integrated policy framework: Evidence from Mongolia - Gan-Ochir Doojav; Munkhbayar Gantumur (Graduate Institute of International and Development Studies, 2023)
This paper develops an estimated New Keynesian model of a commodity-exporting economy for an integrated policy framework, integrating the full range of policies used in practice and featuring a range of nominal and real rigidities, macro-financial linkages, and transmission channels of external shocks. We jointly examine the optimal conduct of conventional and unconventional monetary policies, macroprudential policy, foreign exchange intervention, capital flow management, and fiscal policy based on the model. The policy analysis framework is applied empirically to Mongolia, a small open, and developing economy highly dependent on imports and commodity exports. We find that an eclectic policy mix improves policy tradeoffs, and a lack of cooperation among policy authorities may result in conflicting policies, hence suboptimal results for overall economic stability. Our optimal policy analysis shows that policy mix adjustments should differ depending on the type of shocks and the policy objectives. The results suggest that the policy analysis framework can help policymakers choose their policy mix adjustments to deal with external shocks in an integrated and optimal way.
Keywords: C11; C32; E32; E43; E52; F41; 330; Monetary policy; Macroprudential policy; Foreign exchange intervention; Fiscal policy; Capital flow management; Optimal policy mix; Open economy macroeconomics; External shocks; Bayesian analysis